Perlindungan Data Pribadi dalam Proses Pemutakhiran Data Pemilih Pilkada 2024 di Kota Denpasar - Sahadewa, Anak Agung Gede Ananta Wijaya; Senastri, Ni Made Jaya (Badan Riset dan Inovasi Daerah Provinsi Bali, 2024)
Purpose: This article aims to analyze the protection of personal data in updating voter data for the Pilkada (regional head election) 2024 in Denpasar City. However, advances in digital technology that support election management present new challenges in terms of personal data security. The 2019 voter data leakage incident experienced by the Indonesian KPU makes the critical need for robust data protection measures in the election process. Research methods: This research employs a normative juridical method with both statute and conceptual approaches, analyzing data protection regulations such as Law No. 27 of 2022 and KPU Regulation No. 7 of 2024. Results and discussion: The findings reveal that the voter data updating process involves complex stages, including data matching and verification (coklit) conducted by 1,941 Voter Data Updating Officers in Denpasar City. Protecting personal data is crucial, as leaks could undermine the integrity and public trust in democracy. Implications: The research recommends improving training and supervision for data updating officers, strengthening data protection regulations, and leveraging technology to secure voter data. KPU and related institutions are advised to focus on data integrity by employing e-coklit applications and secure information systems. These measures are expected to maintain voter privacy and support a fair and transparent democratic process.